ANALISIS ANALISIS SOAL ASESMEN SUMATIF AKHIR SEMESTER GANJIL BERBASIS R STUDIO - Minarti Ja'far; Abdul Wahab (At Turots: Jurnal Pendidikan Islam, 2024)
This study aims to measure the quality of summative assessment items at the end of the odd semester of Islamic Religious Education and Budi Pekerti subjects for class XI A students in the 2023-2024 academic year at Al Mumtaz Pontianak Integrated Islamic Senior High School. Islamic Religious Education and Ethics learning carried out at the secondary level must be able to transform into quality learning. Quality learning will be achieved if the learning process starting from planning, implementing and evaluating learning is well designed and implemented by educators. It is very important for educators to evaluate learning. This is done so that the achievement of learning outcomes can be measured. This research method uses a descriptive quantitative approach. The subjects in this study were students of class XI A with a population of 19 students of class XI A. The variables of this study were the level of difficulty, differentiating power, effectiveness of triggers and the level of validity of odd ASAS questions. Data collection techniques are carried out with documentation in the form of questions, grids for writing questions, and answer sheets of odd ASAS students in the 2023-2024 academic year. Data analysis techniques using R software. 4.3.1 and R Studio. The results of the analysis show that the quality of the odd semester summative assessment questions shows 88% or 22 questions out of 25 ASAS questions with 17 questions at a good level as much as 68% and 5 questions with a fairly good level as much as 20%, and the results of the ASAS question reliability test with the results of 0.830 are at a good level, so that the question is feasible to be used as an evaluation instrument or feasible to use in the End of Odd Semester Summative Assessment of Islamic Religious Education and Budi Pekerti subjects for class XI A students at SMAIT AL MUMTAZ Pontianak.